RETURN ON ASSET : CURRENT RATIO AND DEBT TO ASSET RATIO COMPANIES IN INDONESIA STOCK EXCHANGE - Muhammad Irsan; Muis Fauzi Rambe (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
The goal to be achieved in this study is to analyze and determine the effect of the Current Ratio variable on the Return On Asset variable in food and beverage companies on the Indonesia Stock Exchange for the 2014-2018 period. To analyze and determine the effect of the Total Debt to Total Assets Ratio variable on the Return On Assets variable in food and beverage companies on the Indonesia Stock Exchange for the 2014-2018 period. To analyze and determine the effect of Current Ratio and Debt to Assets Ratio on Return On Assets in food and beverage companies on the Indonesia Stock Exchange for the period 2014-2018. In this study, quantitative descriptive data is used which aims to carry out an associative approach. The results of the study showCurrent ratiosignificant positive effect on Return on Assets in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. Debt to Asset Ratio has a significant positive effect on Return on Assets in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period.Current Ratio and Debt to Asset Ratio jointly have a significant positive effect on Return on Assets in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period.